A dual approach to understanding information networks. (1st January 2002) - Assimakopoulos, Dimitris; Macdonald, Stuart
This paper focuses on the interplay between formal interorganisational networks and personal informal networks in IT innovation. It also explores the complementarities between two theoretical perspectives of social and economic networks. The context within which this research is located is Esprit, the European Strategic Programme for Research in IT. The empirical evidence is based on a success story of a UK main contractor in Esprit. The main finding is that formal collaboration networks in Esprit emerge out of informal personal networks, rather than vice versa .